Structure and Function of the Respiratory System - Alvarado, Alcibey (European Journal of Applied Sciences, 2025)
The atmosphere is a mixture of gases that surround any celestial body that has sufficient gravitational force to prevent the gases from escaping from their environment. At first probably it consisted of volcanic emanations with almost no oxygen. The appearance of oxygen in the atmosphere enabled aerobic life as we know it today. The original gill system of fish was replaced by lungs when oxygen dissolved in seawater was converted into the gaseous state of the atmosphere. The respiratory system developed and evolved over eons to serve its most ancient function: gas exchange. The structure of the respiratory system is designed to serve this function. Other functions subsequently emerged during evolutionary development. Cellular respiration, in the intimacy between the capillary and the cell, and external respiration are discussed to understand the architectural design serving this and other functions of the respiratory system.